Saikat Majumdar's The Firebird: A Close Reading. Issue 1 (June 2021) - Datta, Ketaki
The article is an insightful and incisive reading of Professor Saikat Majumdar's second novel, "The Firebird". In a colloquial style, the critic starts off with her acquaintance with the novel and goes deep into the characters. By way of critically appreciating the work, she also brings up comparison with other novels of similar interests and shows how this novel is different from them. After all, culture and identity matter the most while judging the characters in all their intents and purposes.